Neuregulin 3 and its roles in schizophrenia risk and presentation. Issue 2 (29th May 2017) - Avramopoulos, Dimitrios
Abstract : Neuregulins, a four‐member family of epidermal growth factor‐like signaling molecules, have been studied for over two decades. They were first implicated in schizophrenia in 2002 with the detection of linkage and association at the NRG1 locus followed after a few years by NRG3 . However, the associations with disease have not been very consistently observed. In contrast, association of NGR3 variants with disease presentation, specifically the presence of delusions, has been more consistent. This appears to be mediated by quantitative changes in the alternative splicing of the gene, which has also been consistently observed. Additional diseases and phenotypes, psychiatric or not, have also been connected with NRG3 . These results demonstrate two important aspects of behavioral genetics research. The first is that if we only consider simple risk and fail to examine the details of each patient's individual phenotype, we will miss important insights on the disease biology. This is an important aspect of the goals of precision medicine. The second is that the functional consequences of variants are often more complex than simple alterations in levels of transcription of a particular gene, including, among others, regulation of alternative splicing. To accurately model and understand the biological consequences of phenotype—associated genetic variants, we need to study the biological consequences of each specific variant. Simply studying the consequences of a null allele of the orthologous gene in a model system, runs the risk of missing the many nuances of hypomorphic and/or gain of function variants in the genome of interest.